Cimento de alfa-fosfato tricálcico de dupla pega no preenchimento de cavidade anoftálmica - Estudo clínico - Oriá, Arianne Pontes; Dórea Neto, Francisco de Assis; dos Santos, Luis Alberto; Laus, José Luiz [UNESP]; Gomes Junior, Deusdete Conceição (My University, 2014)
The double-setting alpha-tricalcium phosphate bone cement was evaluated as an orbital implant for filling the anophthalmic cavity of dogs. The animals were from the Ophthalmology Unit of the Veterinary Hospital, Universidade Estadual Paulista - Jaboticabal, and from a private veterinary clinic. The study was conducted during two years. The patients' age ranged from 2-11 years old, and their weight from 9-50 kg. The implants ranged from 19 to 25 mm in diameter. Local edema was observed in all animals during the immediate postoperative period. Of the ten performed surgeries in seven animals, a satisfactory, aesthetic result was observed in nine (90%) while in one (10%) of them it was unsatisfactory due to complications that led to the implant removal. The use of the double-setting alpha-tricalcium phosphate bone cement to fill anophthalmic sockets is feasible and could be an alternative to improve the cosmetic appearance after eyeball removal.
Double-setting α-tricalcium phosphate cement for the completion of anophthalmic cavity - Clinical study
Keywords: Artificial eye; Enucleation eye; Hydroxyapatite